PALLIATIVE CARE FOR PATIENTS WITH ONCOLOGICAL WOUNDS IN A TEACHING HOSPITAL: AN EXPERIENCE REPORT - Maria Cristina Freitas de Castro; Pamella da Silva Cruz; Marianne dos Santos Grellmann; Willian Alves dos Santos; Patricia dos Santos Claro Fuly (Universidade Federal do Paraná, 2014)
This study aimed to describe the care provided in the palliative care outpatient center, for the patient with an oncological wound in a federal university teaching hospital in the municipality of Niterói in the state of Rio de Janeiro (RJ), certified as a High Complexity Oncology Center. It was undertaken through observation of the nursing actions in the implementation of the National Cancer Prevention and Control Policy. The complexity of the care for the oncological wounds requires technical and relational competence, addressing the physical, psychological, social and spiritual dimensions, essential for the quality of life of the patient and their family. The outpatient center began its activities in 2005; in October 2014 it had a mean of 70 patients being attended, with 12 new patients entering each month. Recognizing the challenges inherent to decision taking in this proposal of care regarding the needs of the patient, and providing appropriate support for the patient and caregiver, are important aspects if one is to provide efficacious care.